A desperate hope - Camden, Elizabeth, 1965- (Bethany House Publishers, a division of Baker Publishing Group, 2019)
A female accountant in 1908, Eloise Drake thought she'd put her past behind her. Then her new job lands her in the path of the man who broke her heart. Alex Duval, mayor of a doomed town, can't believe his eyes when he sees Eloise as part of the entourage that's come to wipe his town off the map. Can he convince her to help him--and give him another chance?